Electroplating of Nanostructures - Aliofkhazraei, Mahmood (IntechOpen, 2015)
The electroplating was widely used to electrodeposit the nanostructures because of its relatively low deposition temperature, low cost and controlling the thickness of the coatings. With advances in electronics and microprocessor, the amount and form of the electrodeposition current applied can be controlled. The pulse electrodeposition has the interesting advantages such as higher current density application, higher efficiency and more variable parameters compared to direct current density. This book collects new developments about electroplating and its use in nanotechnology.